Unveiling the Dynamics: A Comprehensive Exploration of Formal Learning in Second Language Acquisition Theory: English - Mislawiyadi Mislawiyadi (JOEY: Journal of English Ibrahimy, 2024)
Unveiling the Dynamics: A comprehensive exploration of formal learning in second language acquisition theory was a multidisciplinary research endeavor to unravel the intricate processes and dynamics underlying the acquisition of a second language within formal educational settings. That was grounded in cognitive, socio-cultural, and pedagogical perspectives. This research adopted an integrative approach to provide a holistic understanding of the complex journey of language learning. The cognitive dimension of the study investigated mental processes involved in second language acquisition, drawing on cognitive theories, psycholinguistics, and neuro-educational insights. The socio-cultural exploration delved into the influences of cultural contexts, social interactions, and educational environments on linguistic development, recognizing language learning as a socially embedded phenomenon. This research evaluated pedagogical approaches, synthesizing educational theories and empirical studies to discern effective instructional strategies within formal language education and captured the empirical diverse experiences of teaching and language learning. The comprehensive exploration presented in this research contributes valuable insights to the field of second language acquisition theory, offering a foundation for further research and the development of effective language learning pedagogies. The integration of diverse perspectives and the recognition of the intricate dynamics involved in formal learning highlight the complexity of the language acquisition process and provide a basis for informed educational practices in second language acquisition instructions.